2015
DOI: 10.1016/j.jval.2015.03.1770
|View full text |Cite
|
Sign up to set email alerts
|

The availability and Expenditure of Orphan Medicines in Poland

Abstract: By disease: ischemic heart disease, 1.9 times or 10 days longer; hypertension 1.3 times or 4 days longer; congestive heart failure, 1.2 times or 3 days longer; and rheumatoid arthritis, 1.4 times or 2 days longer. Obese patients with diabetes and s/p cerebral vascular accident had a shorter LOS (0.8 times or 3 days, and 0.8 times or 4 days respectively). CONCLUSIONS: Obesity increases the LOS for all-cause hospital admissions among patients with various underlying chronic diseases. This may be due to insuffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Th e budget impact of orphan drugs represented 2.5% of total drug expenditure in Sweden and 3.1% in France in 2012 [62]. Th e share of orphan drugs in total pharmaceutical market in 2013 reached 3.6% in Czech Republic [26] and 3.2% in Poland [27]. [23].…”
Section: Volume 3 • Number 3 • October 2016 • Hophmentioning
confidence: 99%
See 1 more Smart Citation
“…Th e budget impact of orphan drugs represented 2.5% of total drug expenditure in Sweden and 3.1% in France in 2012 [62]. Th e share of orphan drugs in total pharmaceutical market in 2013 reached 3.6% in Czech Republic [26] and 3.2% in Poland [27]. [23].…”
Section: Volume 3 • Number 3 • October 2016 • Hophmentioning
confidence: 99%
“…Studies conducted in various countries reported that share of orphan drug expenditure had increased since introduction of orphan drug legislation [10,18,[23][24][25][26][27][28]. However, this share represented mainly low percentage (less than 8%) of overall drug expenditure [10,18,[23][24][25][26][27][28]. Picavet et al observed that principal determinants in the market uptake of orphan drugs across 23 countries in Europe were the gross domestic product and the availability of a formal technology assessment organization [29].…”
Section: Introductionmentioning
confidence: 99%